Degradation phenomena on last generations of polyethylene terephthalate knitted vascular prostheses - Arielle Bellissard, MD; Nabil Chakfe, MD, PhD; Salomé Kuntz, MD, MSc; Delphine Dion, MSc; Lory Schmitt; Frédéric Heim, PhD; Anne Lejay, MD, PhD (JVS - Vascular Science, 2023)
Objectives: The aim of this study was to analyze a series of new generations of explanted knitted polyethylene terephthalate (PET) vascular grafts (VGs) presenting nonanastomotic degradations according to preoperative computed tomography angiography (CTA) when available in order to better understand the mechanisms leading to rupture. Methods: Explanted knitted PET VGs were collected as part of the Geprovas European Collaborative Retrieval Program. VGs implanted after 1990 presenting a nonanastomotic rupture of the fabric were included. Clinical data and pre-explantation CTA data when available were retrieved for each VG. The ruptures were characterized by macroscopic examination and optical microscopy according to a standardized protocol. Results: Nineteen explants were collected across 11 European centers, 13 were implanted as infrainguinal bypasses, 3 at the aortic level, and 1 as an axillobifemoral bypass. The mean implantation duration was 9.2 years. Pre-explantation CTA data were available for 8 VGs and showed false aneurysms at the adductor canal level on 4 VGs, at the inguinal ligament level on 2 VGs, and in the proximal or middle third thigh level on 3 VGs. Examination revealed longitudinal ruptures on 9 explanted VGs (EVGs), transversal ruptures on 15 EVGs, 45°-oriented ruptures on 5 EVGs, V-shaped ruptures on 7 EVGs, and punctiform ruptures on 2 EVGs. Ruptures involved the remeshing line on 11 EVGs, the guideline on 10 EVGs, and the crimping valley on 15 EVGs.At the microscopic level, two main degradation phenomena could be identified: a decrease in the density of the meshing and local ruptures of the PET fibers. Fourteen EVGs presented a loosening of the remeshing line and 17 EVGs an attenuation of the crimping. Conclusions: New-generation PET VG degradation seems to result from both anatomic constraints and intrinsic textile structure phenomena. : Clinical Relevance: In this study, the analysis of explanted new-generation polyethylene terephthalate grafts presenting nonanastomotic lesions allowed the identification of two main degradation phenomena: a decrease in the density of the meshing and local ruptures of the polyethylene terephthalate fibers. This highlights that both anatomic constraints and intrinsic textile structure phenomena are involved in degradation phenomena. This study highlights the need to keep studying the degradation mechanisms in order to develop compliant and durable vascular substitutes.